(untitled) (Research, Society and Development, 2019)
In view of the current scenario where environmental concern has become a protagonist, soil stabilization with the addition of lime and cement has emerged as an alternative, sustainable and viable form of application in civil construction. In this way, this work has the objective of studying the chemical stability of the soil, adding cement and lime, in a soil of medium texture with 25% of clay, in order to improve it mechanically to favor its application in soil-cal- cement, the ecological bricks. To proceed, tests were performed varying the percentage of cement and lime in amounts of 0 to 13% in relation to the soil mass. The work procedures are related to soil preparation, analysis of volumetric variation through physical-chemical test, modeling and rupture of test specimens. In the volumetric variation, the samples of 3% of lime presented regular behavior on the trend curve according to the percentage variation of cement. From the mechanical tests, the batches with 3% of lime to 7% and 9% of cement were the only ones that presented average mechanical resistance higher than the minimum established by NBR 8491. At the end of the experiments it can be verified that the variation 3% of lime to 7% of cement on soil mass, was shown to have satisfactory results for the production of soil-cement-brick because it presented superior resistance to the minimum normalized and because it is more economically viable in terms of market prices for lime and cement , than with 9% cement.